Overview of early cretaceous gold mineralization in the orogenic belt of the eastern margin of the Siberian craton: geological and genetic features - Goryachev, Nikolay; Fridovsky, Valery (Frontiers in Earth Science, 2024)
The article is a review, supplemented by the authors' data, of the Early Cretaceous gold orogenic mineralization known in the Yana-Kolyma and Okhotsk-Koryak fold belts of the Siberian craton eastern framing. It is represented by Au-As and Au-Sb types of mineralization. The article characterizes the tectonic, geochronological, mineralogical, and geochemical features of ores on the example of typical ore deposits (Nezhdaninskoye, Marinskoye, Vetrenskoye, Sarylakh) and shows the mineralogical and geochemical specificity of ore mineralization of deposits of the Yana-Kolyma orogenic belt, which distinguishes them from the same-age deposits of the Allah-Yun zone of the Okhotsk-Koryak orogenic belt. A preliminary model of the origin of mineralization of this stage is proposed in connection with the processes of the Okhotsk-Koryak orogenic belt formation. This mineralization within the Yana-Kolyma orogenic belt assumingly appeared due to dehydration of the submerged slab and local upwelling in the mantle in the rear of the active continental margin. The possibility of the gold-bearing fluids existence in such conditions is estimated. zone (AYuZ), also turned out to be the Early Cretaceous 125-118 Ma (Borisenko et al., 2012;Bakharev et al., 2011). Consequently, in generalizing publications (Goldfarb et al., 2014; Goryachev, Pirajno, 2014), two stages in orogenic gold deposit formation were identified for the territory of Northeast Asia: early (Late Jurassic-Early Cretaceous), chronologically related to the final of the Late Mesozoic orogenic event, and late (Early Cretaceous, namely Aptian-Albian) related to the processes of the Okhotsk-Koryak (OKOB) or Oloy-Chukotka orogenic belts formation (